The Humanities [videorecording] what they are and what they do - Rinner, Floyd; Massachusetts Council for the Humanities ([S.l.] The Council)
Discusses the importance of humanities. Describes the ways in which civilized western man has recorded his hopes, fears, joys and sorrows, his vast guesses about his relations to the world, to other man, to his past and to God.
VHS.
Host, Clifton Fadiman.
Keywords: Humanities; Humanity